Interprofessional Collaboration in Health Care: Clinical Pharmacists’ Brokering Activities in Medication Reviews - Ingebrigtsen, Stine Agnete; Lundvoll Warth, Line (Professions and professionalism, 2025)
In hospitals, several professions collaborate on patients’ medication treatment. We explore clinical pharmacists’ work and ask what opportunities and challenges arise when clinical pharmacists participate in interprofessional medication reviews. Findings from observations and interviews in two hospitals reveal that medications were discussed in greater depth in pre-rounds where clinical pharmacists were present as they negotiated medication treatment, leading to collaboration with physicians and boosting nurses’ engagement. Clinical pharmacists’ brokering activities created knowledge-sharing opportunities and aligned perspectives across professional boundaries. However, clinical pharmacists also experienced challenges being heard by physicians, highlighting professional conflicts regarding jurisdictional claims to medication decisions. This challenge was accentuated by a lack of adaptation for clinical pharmacists’ occupational role on a structural level. We argue for consistent adaptation for clinical pharmacists’ occupational roles to support their professional jurisdiction and utilise comprehensive work practices in medication treatment.